Wien Wien 1960-1990 - Sotriffer, Kristian; Rychlik, Otmar; Museum für Moderne Kunst, Bozen (Milano : Nuove Edizioni Gabriele Mazzotta, 1989)
Adrian, Marc ; Anzinger, Siegfried ; Attersee, Christian Ludwig ; Blau, Luigi ; Bloyer, Karl Heinz ; Bohatsch, Erwin ; Brandl, Herbert ; Brus, Günter ; Caramelle, Ernst ; Cibulka, Heinz ; Himmelblau, Coop ; Czech, Hermann ; Dunst, Heinrich ; Eisler, Georg ; Fink, Tone ; Fleck, Karl Anton ; Frohner, Adolf ; Gironcoli, Bruno ; Goeschl, Roland ; Graf, Franz ; Graf & Zyx ; Herzig, Wolfgang ; Hofleitner, Rudolf ; Hrdlicka, Alfred ; Jascha, Johann ; Jürgenssen, Birgit ; Jungwirth, Martha ; Kabas, Robert ; etc.
Wien Wien 1960-1990, Castel Ivano, Valsugana, 20 juli - 3 september 1989. Museum für Moderne Kunst, Bozen, 1989
Duits
kunstcatalogus
Keywords: Wenen